Does coastal armoring affect biodiversity and its functional composition on sandy beaches?. (November 2022) - Laurino, Ivan R.A.; Checon, Hélio H.; Corte, Guilherme N.; Turra, Alexander
Abstract: Sandy beaches are increasingly squeezed due to the construction of backshore man-made structures (i.e., coastal armoring) and current global changes. Coastal armoring impacts beach sediment dynamics, inducing erosion and habitat loss, threatening biodiversity processes and the functional roles of sandy beach organisms. Here, we examine how the abundance, taxonomic richness, and functional richness of sandy beach fauna are affected by coastal armoring. We compared macrobenthic infaunal communities on five armored beaches (with backshore urban structures) and five vegetated beaches (not-armored). We also evaluated the abundance and biomass of upper-beach arthropods using pitfall traps, comparing armored and vegetated segments within the beaches. Infaunal richness and abundance were lower at armored beaches, mainly in the subtidal zones, because of a reduction in polychaete and molluscan abundance. There was no difference in overall functional richness between the armored and vegetated beaches. Nevertheless, we found that functional groups such as small suspension feeders were more associated with armored beaches, while large-bodied species and predators were more frequent at vegetated beaches. Pitfall traps showed that coastal armoring also reduced the abundance of the upper-beach coleopteran Phaleria testacea, leading to a loss of biomass. Therefore, our data suggest that coastal armoring can influence the functional composition of sandy beach biodiversity and significantly impact macrobenthic abundance and biomass. Highlights: Sandy beaches are increasingly squeezed due to coastal armoring and global changes. We tested how coastal armoring affects macrofauna composition and functioning. Coastal armoring reduced the abundance of polychaetes, molluscans and coleopterans. Species with large body sizes, high motility and predators were negatively affected. Coastal armoring threatens the functional structure and biomass stock on beaches.